INDONESIA’S INTERFERENCE IN TRANSLATING TEXT INTO ENGLISH TEXT - Etika Ariyani (Muhammadiyah University of Mataram, 2015)
This research is aimed: (1) to reveal that interference of Indonesian language interrupt when the students at the sixth semester of FKIP in Muhammadiyah University of Mataram translate the English narrative past tense text; (2) to know the kinds of factors interrupted the students’ in translating English narrative the text. The population of study were students in FKIP Muhammadiyah University of Mataram. They consist of three classes from class A to C. The number of the population was 64 students so, the writer took only the 17 students as the samples, by using purposive sampling technique. The results of the research showed that: (1) among 17 students in class A do some interferences, they have less ability to construct the translation target text into the accuracy, acceptable and understandable/ readable sentences by the reader. Moreover, there are two main Indonesian interference found by the researcher, they were morphological interference by misunderstanding of using past tense sentences and syntactical interference by unstructured sentence in the target text, (2) The students’ only could get the range from 4 scores to 8 scores, where 5 students get very poor, 4 students get poor, 2 students get fair, 3 students get fairly good, 3 students get good. The students’ translation percentage for each standard such as accuracy is 16,5%, acceptable is 10,11%, readability is 5,47% and for total all of the students’ mean score is 51,9%, where it took on poor score of translation (3) There are 4 factors made the students difficult to translate the target text, they were 1. Disloyalty of the speakers and receiver 2 Insufficient of vocabulary in translating the source language into the target language, 3. The prestige of the source language and style, 4. Daily habits in the mother tongue influence target text, (4) The students’ translations result are 6 students got score of 0-3 namely very low level, 6 students got score of 5,5-6,5, who categorized as the low level, 2 students got the range score of 6,6-7,5, who categorized “sufficient level”, there are 3 students got this “high level” with the range score of 7,6-9,5, and no one getting the “highest level” score in the range of 9,6-10.